MENINGKATKAN KEPUTUSAN PEMBELIAN MELALUI STRATEGI POSITIONING PRODUCT, DAN PERCEIVED QUALITY YANG DIPENGARUHI OLEH INOVASI PRODUK - Putra, Laksmana Pratama; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2015)
Rapid technological developments have changed in dynamic environment. Replication of the quality products also can be done easily by competitors. Nokia the biggest smartphone developers, not even able to compete and continue to loss and eventually sold his company to Microsoft in 2014. This study aims to determine whether the product innovation is able to create the perceived of quality, and product positioning strategies have an impact on the purchase decision of Microsoft Lumia windows phone.This research was conducted by questionnaire survey. The sample used was a potential buyer at the counter smartphone as many as 130 people. The data processed using multiple regression analysis.The results showed that two independent variables directly influencing purchase decision variables. Variable product innovation has direct influencing to perceived quality variables and indirectly influencing purchase decisions. Consistent with the previous studies, perceived quality has a positive and significantly influence on the purchase decision variables and acts as an intervening variable.